PENGARUH BAHAN AJAR MUATAN LOKAL PENINGGALAN SEJARAH TERHADAP HASIL BELAJAR KOGNITIF SISWADI KELAS V SD NEGERI 74 KOTA BENGKULU - Lukman Lukman; Dwi Anggraini; Susi Susanti (JURIDIKDAS, 2018)
This Reseacrh aimed to know the impact of apllying teaching materials of local content historical heritage towards students cognitive learning result of grade V students SD Negeri 74 Kota Bengkulu. This research used quantitative pre-experimen method, with one group pretest-posttest design which was done at the 5th grade students SD Negeri 74Kota Bengkulu. The population of this research was the 5th Grade students SD Negeri 74 Kota Bengkulu which consisted of 131 students. The sample of the research was taken by using cluster random sampling technic, so all of the students at VA class was conducted as the sample for this research. The techichs of collecting the data on this research was done by doing pretest-posttest which consisted of 30 objective questions. The results of t test was ttest 5,905 > ttabel 1,697 with 5% significancy which showed there was a significance effect on the students cognitive learning results. Based on the data analyzing that ttest> ttabel means alternatif hypotesys has accepted. The conclusion was There were some effects of teaching material local content historical heritage towards the cognitive learning results on 5th grade students of SD Negeri 74 Kota Bengkulu.